(untitled) (Perner’s Contacts, 2011)
The article summarizes statistical data from the Czech Republic about public line transport and stops designated for provision of transport services. The article presents segmentation of stops and gives a definition of their tasks. The main part of the article describes stops problems and gives proposals to their solutions in location and identification, wheelchair accessible, technical condition, cleanness and amenities.